Acute hepatitis as a manifestation of primary HSV infection in a healthy child - Elena Virginia Comi; Paola Bruni; Dimitri Poddighe (Hygeia Press di Corridori Marinella, 2019)
Several herpesviruses can cause hepatic injury, but herpes simplex virus (HSV) is rarely involved in immune-competent patients, beyond the neonatal age. We report a rare case of acute hepatitis associated with primary HSV infection in a previously healthy child. Therefore, HSV infection should be actively investigated in healthy children developing acute hepatitis without acute liver failure, if the most common infectious agents have been excluded, despite the absence of the typical vesicular herpetic skin and/or mucosal manifestations.